Synopsis of the pelidnotine scarabs (Coleoptera, Scarabaeidae, Rutelinae, Rutelini) and annotated catalog of the species and subspecies - Moore, Matthew R.; Jameson, Mary L.; Garner, Beulah H.; Audibert, Cédric; Smith, Andrew B. T.; Seidel, Matthias (2017)
The pelidnotine scarabs (Scarabaeidae: Rutelinae: Rutelini) are a speciose, paraphyletic assemblage of beetles that includes spectacular metallic species (“jewel scarabs”) as well as species that are ecologically important as herbivores, pollinators, and bioindicators. These beetles suffer from a complicated nomenclatural history, due primarily to 20th century taxonomic and nomenclatural errors. We review the taxonomic history of the pelidnotine scarabs, present a provisional key to genera with overviews of all genera, and synthesize a catalog of all taxa with synonyms, distributional data, type specimen information, and 107 images of exemplar species. As a result of our research, the pelidnotine leaf chafers (a paraphyletic group) include 27 (26 extant and 1 extinct) genera and 420 valid species and subspecies (419 extant and 1 extinct). Our research makes biodiversity research on this group tractable and accessible, thus setting the stage for future studies that address evolutionary and ecological trends. Based on our research, 1 new species is described, 1 new generic synonym and 12 new species synonyms are proposed, 11 new lectotypes and 1 new neotype are designated, many new or revised nomenclatural combinations, and many unavailable names are presented. The following taxonomic changes are made: New generic synonym: The genus Heteropelidnota Ohaus, 1912 is a new junior synonym of Pelidnota MacLeay, 1819. New species synonyms: Plusiotis adelaida pavonacea Casey, 1915 is a syn. n. of Chrysina adelaida (Hope, 1841); Odontognathus gounellei Ohaus, 1908 is a revised synonym of Pelidnota ebenina (Blanchard, 1842); Pelidnota francoisgenieri Moore & Jameson, 2013 is a syn. n. of Pelidnota punctata (Linnaeus, 1758); Pelidnota genieri Soula, 2009 is a syn. n. of Pelidnota punctata (Linnaeus, 1758); Pelidnota lutea (Olivier, 1758) is a revised synonym of Pelidnota punctata (Linnaeus, 1758); Pelidnota (Pelidnota) texensis Casey, 1915 is a revised synonym of Pelidnota punctata (Linnaeus, 1758); Pelidnota (Strigidia) zikani (Ohaus, 1922) is a revised synonym of Pelidnota tibialis tibialis Burmeister, 1844; Pelidnota ludovici Ohaus, 1905 is a syn. n. of Pelidnota burmeisteri tricolor Nonfried, 1894; Rutela fulvipennis Germar, 1824 is syn. n. of Pelidnota cuprea (Germar, 1824); Pelidnota pulchella blanda Burmeister, 1844 is a syn. n. of Pelidnota pulchella pulchella (Kirby, 1819); Pelidnota pulchella scapularis Burmeister, 1844 is a syn. n. of Pelidnota pulchella pulchella (Kirby, 1819); Pelidnota xanthogramma Perty, 1830 is a syn. n. of Pelidnota pulchella pulchella (Kirby, 1819). New or revised statuses: Pelidnota fabricelavalettei Soula, 2009, revised status, is considered a species; Pelidnota rioensis Soula, 2009, stat. n., is considered a species; Pelidnota semiaurata semiaurata Burmeister, 1844, stat. rev., is considered a subspecies. New or comb. rev. and revised status: Plusiotis guaymi Curoe, 2001 is formally transferred to the genus Chrysina (C. guaymi (Curoe, 2001), comb. n.); Plusiotis transvolcanica Morón & Nogueira, 2016 is transferred to the genus Chrysina (C. transvolcanica (Morón & Nogueira, 2016), comb. n.). Heteropelidnota kuhnti Ohaus, 1912 is transferred to the genus Pelidnota (P. kuhnti (Ohaus, 1912), comb. n.); Odontognathus riedeli Ohaus, 1905 is considered a subspecies of Pelidnota rubripennis Burmeister, 1844 (Pelidnota rubripennis riedeli (Ohaus, 1905), revised status and comb. rev.); Pelidnota (Strigidia) acutipennis (F. Bates, 1904) is transferred to the genus Sorocha (Sorocha acutipennis (F. Bates, 1904), comb. rev.); Pelidnota (Odontognathus) nadiae Martínez, 1978 is transferred to the genus Sorocha (Sorocha nadiae (Martínez, 1978), comb. rev.); Pelidnota (Ganonota) plicipennis Ohaus, 1934 is transferred to the genus Sorocha (Sorocha plicipennis (Ohaus, 1934), comb. rev.); Pelidnota similis Ohaus, 1908 is transferred to the genus Sorocha (Sorocha similis (Ohaus, 1908), comb. rev.); Pelidnota (Ganonota) yungana Ohaus, 1934 is transferred to Sorocha (Sorocha yungana (Ohaus, 1934), comb. rev.); Pelidnota malyi Soula, 2010: 58, revised status; Xenopelidnota anomala porioni Chalumeau, 1985, revised subspecies status. To stabilize the classification of the group, a neotype is designated for the following species: Pelidnota thiliezi Soula, 2009. Lectotypes are designated for the following names (given in their original combinations): Pelidnota brevicollis Casey, 1915, Pelidnota brevis Casey, 1915, Pelidnota debiliceps Casey, 1915, Pelidnota hudsonica Casey, 1915, Pelidnota oblonga Casey, 1915, Pelidnota pallidipes Casey, 1915, Pelidnota ponderella Casey, 1915, Pelidnota strenua Casey, 1915, Pelidnota tarsalis Casey, 1915, Pelidnota texensis Casey, 1915, and Scarabaeus punctatus Linnaeus, 1758. The following published infrasubspecific names are unavailable per ICZN Article 45.6.1: Pelidnota (Odontognathus) cuprea var. coerulea Ohaus, 1913; Pelidnota (Odontognathus) cuprea var. rufoviolacea Ohaus, 1913; Pelidnota (Odontognathus) cuprea var. nigrocoerulea Ohaus, 1913; Pelidnota pulchella var. fulvopunctata Ohaus, 1913; Pelidnota pulchella var. sellata Ohaus, 1913; Pelidnota pulchella var. reducta Ohaus, 1913; Pelidnota unicolor var. infuscata Ohaus, 1913. The following published species name is unavailable per ICZN Article 11.5: Neopatatra synonyma Moore & Jameson, 2013. The following published species name is unavailable per application of ICZN Article 16.1: Parhoplognathus rubripennis Soula, 2008. Synopsis of the pelidnotine scarabs (Coleoptera, Scarabaeidae, Rutelinae, Rutelini) 3 The following published species name is unavailable per application of ICZN Article 16.4.1: Strigidia testaceovirens argentinica Soula, 2006, Pelidnota (Strigidia) testaceovirens argentinica (Soula, 2006), and Pelidnota testaceovirens argentinica (Soula, 2006). The following published species names are unavailable per application of ICZN Article 16.4.2: Homonyx digennaroi Soula, 2010; Homonyx lecourti Soula, 2010; Homonyx mulliei Soula, 2010; Homonyx simoensi Soula, 2010; Homonyx wagneri Soula, 2010; Homonyx zovii Demez & Soula, 2011; Pelidnota arnaudi Soula, 2009; Pelidnota brusteli Soula, 2010; Pelidnota chalcothorax septentrionalis Soula, 2009; Pelidnota degallieri Soula, 2010; Pelidnota lavalettei Soula, 2008; Pelidnota lavalettei Soula, 2009; Pelidnota dieteri Soula, 2011; Strigidia gracilis decaensi Soula, 2008, Pelidnota (Strigidia) gracilis decaensi (Soula, 2008), and Pelidnota gracilis decaensi (Soula, 2008); Pelidnota halleri Demez & Soula, 2011; Pelidnota injantepalominoi Demez & Soula, 2011; Pelidnota kucerai Soula, 2009; Pelidnota malyi Soula, 2010: 36-37; Pelidnota mezai Soula, 2009; Pelidnota polita darienensis Soula, 2009; Pelidnota polita orozcoi Soula, 2009; Pelidnota polita pittieri Soula, 2009; Pelidnota punctulata decolombia Soula, 2009; Pelidnota punctulata venezolana Soula, 2009; Pelidnota raingeardi Soula, 2009; Pelidnota schneideri Soula, 2010; Pelidnota simoensi Soula, 2009; Pelidnota unicolor subandina Soula, 2009; Sorocha carloti Demez & Soula, 2011; Sorocha castroi Soula, 2008; Sorocha fravali Soula, 2011; Sorocha jeanmaurettei Demez & Soula, 2011; Sorocha yelamosi Soula, 2011; Xenopelidnota bolivari Soula, 2009; Xenopelidnota pittieri pittieri Soula, 2009. Due to unavailability of the name Pseudogeniates cordobaensis Soula 2009, we describe the species as intentionally new (Pseudogeniates cordobaensis Moore, Jameson, Garner, Audibert, Smith, and Seidel, sp. n.).